1994
DOI: 10.1093/ptj/74.4.299
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Gait Characteristics of Patients With Diabetes and Peripheral Neuropathy Compared With Age-Matched Controls

Abstract: The DM group subjects appeared to pull their legs forward using hip flexor muscles (hip strategy) rather than pushing the legs forward using plantar-flexor muscles (ankle strategy), as seen in the NODM group subjects. Implications for treatment are presented to attempt to reduce the number of injuries during walking in patients with DM and peripheral neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
197
1
32

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 294 publications
(257 citation statements)
references
References 24 publications
26
197
1
32
Order By: Relevance
“…Clinical measures of passive ankle DF ROM and stiffness obtained in this study are consistent with previous reports documenting reduced ankle DF ROM [10,26] and increased stiffness [22] in subjects with DM. Changes in ankle DF ROM and stiffness in individuals with DM have been attributed to disease-dependent as well as use-dependent processes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Clinical measures of passive ankle DF ROM and stiffness obtained in this study are consistent with previous reports documenting reduced ankle DF ROM [10,26] and increased stiffness [22] in subjects with DM. Changes in ankle DF ROM and stiffness in individuals with DM have been attributed to disease-dependent as well as use-dependent processes.…”
Section: Discussionsupporting
confidence: 91%
“…Disease-dependent mechanisms involve non-enzymatic glycation of collagen due to the underlying metabolic disorder [11]. Use-dependent mechanisms allude to adaptive fiber shortening within the triceps surae [29]. Qualitative changes in connective tissue stiffness as well as quantitative changes related to changes in the ratio of connective tissue to contractile tissue may contribute to increased ankle stiffness in individuals with DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a number of gait parameters reported by Mueller et al [23] a range was found for the standardised difference of between 1.15 and 1.57. For this power calculation a conservative estimate of the standard difference of 1 was used.…”
Section: Discussionmentioning
confidence: 99%